Kebijakan Sertifikasi Dosen Terhadap Peningkatan Kinerja Dosen Pascasarjana Prodi Pendidikan Agama Islam UIN Ar-Raniry Banda Aceh - Hasanah, Uswatun; Widyanto, Anton (DAYAH: Journal of Islamic Education, 2024)
The purpose of this study was to determine the lecturer certification policy to improve the performance of lecturers in the Islamic Education Study Program of Postgraduate UIN Ar-Raniry Banda Aceh. This research method is descriptive with a qualitative approach, with data collection techniques carried out using library study techniques and field studies, The informants in this study are 1) Lecturers who have passed the certification, 2) Head of the Islamic Education Study Program, 3) Students of the Islamic Education Study Program. The results showed that the implementation of lecturer certification in general is not only limited to fulfilling the obligations of the Lecturer Workload (BKD) but also an effort to improve the quality expected by the Lecturer Certification Program, and lecturers who receive certification benefits support efforts to improve the quality of learning and performance